Identifying Phronotypes in Psychiatry - Kozel, F. Andrew (Frontiers in Psychiatry, 2010)
Refinements in the methods of diagnosis for psychiatric disorders are critically needed. These new methods should be based on objectively measured brain characteristics that provide clinically useful information. Studying the brain with respect to psychiatric disorders, however, faces numerous challenges. Utilizing techniques learned in other areas of medicine to deal with symptoms that lead to complex disorders can provide insight into improving diagnostic models in psychiatry. Specifically, many areas of medicine use objective measures of an organ’s function or characteristic to guide clinical management of particular subjective complaints. In psychiatry, an objectively measured brain characteristic that provides clinically useful information is proposed to be that person’s “phronotype.” Important requirements to developing phronotypes are discussed. Identifying phronotypes in psychiatry will require a specific investigative approach that must be grounded in rigorous scientific methodology. Successfully developing such markers will have a profound impact on clinical care, clinical research, basic science research, and most importantly the lives of those suffering from these illnesses.